Parental Assessment of Infantile Hemangioma Cosmetic Clinical Outcomes: Results of the Spanish Hemangioma Nationwide Prospective Cohort - M. Colmenero-Sendra; J. del Boz-González; E. Baselga Torres; J. Bernabéu-Wittel; E. Roé-Crespo; A. Vicente; M. Valdivieso-Ramos; A. Martín-Santiago; S.I. Palencia-Pérez; M.T. Montserrat-García; A. Azón-Masoliver; M. Dañino; et al. (Actas Dermo-Sifiliográficas)
Background: Functional impairment is the main consideration when it comes to choosing therapy for infantile hemangiomas (IH). However, since most hemangiomas are treated for cosmetic reasons, it is important to know the cosmetic outcome assessed by the parents. Objective: To evaluate the aesthetic outcomes of IH, considering the characteristics of the lesions and the treatments used. Patients and methods: The Spanish Infantile Hemangioma Nationwide Prospective Cohort (2016–2022) recruited all consecutive patients diagnosed with IH in 12 Spanish hospitals. The children included had two photos of the IH lesion (at both baseline and at the end of the study). A panel of parents blindly assessed all available photos using a scale from 0 (worst cosmetic outcomes) to 10 (best cosmetic outcomes). The different scores – both before and after treatment – as well as the outcomes percent considered excellent (>9) were described and compared. We analyzed the effect of receiving different therapies and performed causal model analyses estimating the mean treatment effect of parents’ assessments. Results: The median follow-up was 3.1 years. A total of 824 photos were evaluated. Baseline aesthetic impact was higher in the propranolol group vs the topical timolol and observation treatment groups (1.85 vs 3.14 vs 3.66 respectively; p < 0.001). After treatment, the aesthetic impact was similar between both treatment groups (7.59 vs 7.93 vs 7.90; p > 0.2). The causal model could only be applied to the comparison between topical timolol and observation, revealing no differences whatsoever. Conclusion: This is the first prospective cohort to analyze the aesthetic outcome of IH. The final aesthetic results of the three therapies were similar, with nearly 40% of patients achieving excellent aesthetic outcomes. Resumen: Antecedentes: El compromiso funcional es la principal indicación para iniciar tratamiento en los hemangiomas infantiles (HI). Sin embargo, muchos hemangiomas se tratan por el impacto estético que ocasiona en los niños, por lo que consideramos importante conocer el resultado cosmético evaluado por los padres. Objetivo: Evaluar el resultado estético de los HI, teniendo en cuenta las características de las lesiones y los tratamientos utilizados. Pacientes y métodos: La cohorte prospectiva española de HI (2016-2022) reclutó de manera consecutiva a todos los pacientes diagnosticados con HI en 12 hospitales españoles. A los niños incluidos se les realizaron dos fotografías de la lesión (una basal y otra al final del estudio). Un panel de padres realizó una evaluación ciega de todas las fotos utilizando una escala que iba de 0 (peor resultado cosmético) a 10 (mejor). Se describieron y compararon la diferencia de puntuación antes y después del tratamiento y el porcentaje de resultados considerados excelentes (>9). Se analizó el efecto de recibir diferentes terapias y se realizaron análisis de modelos causales estimando el efecto medio del tratamiento sobre las valoraciones de los padres. Resultados: La mediana de seguimiento fue de 3,1 años. Se evaluaron 824 fotografías. El impacto estético basal fue mayor en los grupos de tratamiento con propranolol que en los de timolol tópico y observación (1,85 vs 3,14 vs 3,66, respectivamente; p < 0,001). Después del tratamiento, el impacto estético fue similar entre los grupos de tratamiento (7,59 vs 7,93 vs 7,90; p > 0,2). El modelo causal solo pudo aplicarse a la comparación entre timolol tópico y observación, sin mostrar diferencias. Conclusiones: Presentamos la primera cohorte prospectiva que analiza el resultado estético de los HI. Los resultados estéticos finales de los tres tratamientos fueron similares, y alrededor del 40% de los pacientes describieron unos resultados estéticos excelentes.